2019
DOI: 10.15766/mep_2374-8265.10816
|View full text |Cite
|
Sign up to set email alerts
|

A Problem-Based Learning Session on Pregnancy Options, Counseling, and Abortion Care

Abstract: Introduction Before their clinical rotations, medical students have limited exposure to women's health issues, particularly abortion. Methods We piloted a problem-based learning (PBL) module to introduce second-year medical students at the University of Louisville School of Medicine to counseling patients about pregnancy options. Students were divided into groups of 10 and met for two 2-hour sessions. In the first session, learners were presented with a case about a wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…In 2019, Pomerantz et al reported introducing a problembased learning module (PBL) to second-and third-year medical students at the University of Louisville School of Medicine. Learners were presented with a case and then asked to develop objectives to research for which they convened with facilitators 1 week later to discuss [17]. The authors noted that only 50% of faculty facilitators reported feeling adequately prepared to facilitate discussions surrounding pregnancy termination [17].…”
Section: Instructional Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 2019, Pomerantz et al reported introducing a problembased learning module (PBL) to second-and third-year medical students at the University of Louisville School of Medicine. Learners were presented with a case and then asked to develop objectives to research for which they convened with facilitators 1 week later to discuss [17]. The authors noted that only 50% of faculty facilitators reported feeling adequately prepared to facilitate discussions surrounding pregnancy termination [17].…”
Section: Instructional Methodsmentioning
confidence: 99%
“…Learners were presented with a case and then asked to develop objectives to research for which they convened with facilitators 1 week later to discuss [17]. The authors noted that only 50% of faculty facilitators reported feeling adequately prepared to facilitate discussions surrounding pregnancy termination [17]. They concluded that a PBL provided students with tools to better counsel patients seeking abortion and that the PBL increased students' knowledge [17].…”
Section: Instructional Methodsmentioning
confidence: 99%
See 3 more Smart Citations